Socio-psychological Characteristics of the Involvement of Students in Continuing Education at Different Stages of the Learning Process - Kiseleva N.V (Moscow State University of Psychology and Education, 2018)
The article presents a substantive analysis of structure patterns of the students' continuing education process throughout different stages: college, bachelor, master, post-graduate, additional education (professional retraining programs). The structure of engagement is described, including cognitive, affective, behavioral, motivational and value components. Each component has been measured by five indicators. The study covers 593 respondents, including college students, bachelor, master or post-graduate, retraining programs. The article reveals the results of substantive analysis. Coherence (integration), divergence (differentiation) of structures, degree of organization of structure patterns for different groups of students are determined; the most significant components of involvement for each group are identified. The results of the research allowed to come to the following conclusion: the differences between the structural patterns of students' involvement throughout different stages of education are substantial and multiple.